Evaluation of Licensing for Food Sales in School Environments: Study of Hazardous Chemical Content - Saragih, Ferdinan; Pratama, Muhammad Rizky; Tama, Gita Citra; Yurinda, Aisyah; Yunita, Sri (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
Food sales within school environments are a critical concern for student health, particularly regarding the potential presence of harmful substances in sold food. This study aims to evaluate the licensing of food sales at SMPN 28 Medan, focusing on identifying hazardous substances. The research methods include a literature review to understand regulations and food safety standards in schools, along with qualitative observations within the school environment to assess compliance with these regulations. Data were collected through interviews with school representatives and food vendors, as well as analysis of food samples to detect harmful substances such as excessive coloring and preservatives. The results of this study are expected to provide an overview of compliance levels with licensing and food safety regulations and offer recommendations for schools to strengthen food sales monitoring to support a healthy environment for students